Magnetic Resonance Texture Analysis in Myocardial Infarction - Peng, Fei; Zheng, Tian; Tang, Xiaoping; Liu, Qiao; Sun, Zijing; Feng, Zhaofeng; Zhao, Heng; Gong, Lianggeng (Frontiers in Cardiovascular Medicine, 2021)
Texture analysis (TA) is a newly arisen field that can detect the invisible MRI signal changes among image pixels. Myocardial infarction (MI) is cardiomyocyte necrosis caused by myocardial ischemia and hypoxia, becoming the primary cause of death and disability worldwide. In recent years, various TA studies have been performed in patients with MI and show a good clinical application prospect. This review briefly presents the main pathogenesis and pathophysiology of MI, introduces the overview and workflow of TA, and summarizes multiple magnetic resonance TA (MRTA) clinical applications in MI. We also discuss the facing challenges currently for clinical utilization and propose the prospect.